Regulation of midgut cell proliferation impacts Aedes aegypti susceptibility to dengue virus. - Mabel L Taracena; Vanessa Bottino-Rojas; Octavio A C Talyuli; Ana Beatriz Walter-Nuno; José Henrique M Oliveira; Yesseinia I Angleró-Rodriguez; Michael B Wells; George Dimopoulos; Pedro L Oliveira; Gabriela O Paiva-Silva (Public Library of Science (PLoS), 2018)
Aedes aegypti is the vector of some of the most important vector-borne diseases like dengue, chikungunya, zika and yellow fever, affecting millions of people worldwide. The cellular processes that follow a blood meal in the mosquito midgut are directly associated with pathogen transmission. We studied the homeostatic response of the midgut against oxidative stress, as well as bacterial and dengue virus (DENV) infections, focusing on the proliferative ability of the intestinal stem cells (ISC). Inhibition of the peritrophic matrix (PM) formation led to an increase in reactive oxygen species (ROS) production by the epithelial cells in response to contact with the resident microbiota, suggesting that maintenance of low levels of ROS in the intestinal lumen is key to keep ISCs division in balance. We show that dengue virus infection induces midgut cell division in both DENV susceptible (Rockefeller) and refractory (Orlando) mosquito strains. However, the susceptible strain delays the activation of the regeneration process compared with the refractory strain. Impairment of the Delta/Notch signaling, by silencing the Notch ligand Delta using RNAi, significantly increased the susceptibility of the refractory strains to DENV infection of the midgut. We propose that this cell replenishment is essential to control viral infection in the mosquito. Our study demonstrates that the intestinal epithelium of the blood fed mosquito is able to respond and defend against different challenges, including virus infection. In addition, we provide unprecedented evidence that the activation of a cellular regenerative program in the midgut is important for the determination of the mosquito vectorial competence.